Water enhanced mechanism for CO2 – Methanol conversion - Rachid Hadjadj; Csizmadia Imre Gyula; Mizsey Peter; Svend Knak Jensen; Viskolcz Béla; Bela Fiser; Fiser Béla; Фішер Бейло (Elsevier, 2020)
Abstract. Carbon dioxide can be converted into fine chemicals such as methanol and thus, the produced renewable energy can be stored in chemical bonds through reductions. To achieve this, a water enhanced mechanism of CO2 hydrogenation leading to methanol has been designed by applying 1:3 (CO2 + 3H2) extended with a water molecule and a hydronium. The thermodynamic properties of the intermediate species and transition states have been calculated by using the W1U composite method. The energy efficiency of the studied mechanism is 27.1%. By understanding the mechanism, special purpose catalysts can be designed to accelerate carbon dioxide conversion.
Editorial board: https://www.sciencedirect.com/journal/chemical-physics-letters/about/editorial-board
Contents: https://www.sciencedirect.com/journal/chemical-physics-letters/vol/746/suppl/C
Keywords: Carbon dioxide hydrogenation; Climate change; Computational study; Energy storage